Bell-and-spigot joints mechanical properties study of PCCP under the uneven settlement of foundation: Simulation and full-scale test. (September 2022) - Wu, Hanying; Zhai, Kejie; Fang, Hongyuan; Wang, Fuming; Yu, Xiang; Li, Bin
Highlights: A fined 3-D FEM model of PCCP is established and evaluated by a full-scale test. Based on the calculation model of fluid–solid coupling, the stress responses of joints are analyzed when uneven settlement occurs in the foundation. Along the hoop direction, the damage extends from the crown to both sides, and along the axial direction, the damage extends from the root of the spigot to both sides. The visible crack will occur in the concrete when the vertical relative displacement is 83 mm, 76 mm, and 83 mm under case 1, case 2, and case 3, respectively. Abstract: Prestressed concrete cylinder pipe (PCCP) makes full use of the compressive and corrosion resistance of concrete and mortar, as well as the tensile and sealing properties of steel, and has good mechanical properties. But the bell-spigot joints are the weak points of the PCCP pipeline and are easy to be damaged. In this study, a fined 3-D FEM model of PCCP is established. Based on the calculation model of fluid–solid coupling, the stress responses of joints are analyzed when uneven settlement occurs in the foundation. The cases of the different interfaces between the two foundation soils are considered. Then, a full-scale test is carried out, and the FEM model is evaluated. The results show that visible crack will occur in the concrete when the vertical relative displacement is 83 mm, 76 mm, and 83 mm under case 1, case 2, and case 3, respectively. And the concrete damage of J3 occurs first at the root of the crown. Along the hoop direction, the damage extends from the crown to both sides, and along the axial direction, the damage extends from the root of the spigot to both sides. And there is a minimum difference of 0.11 % and a maximum difference of 26.59 % between the test and FEM results.